Symmetric boundary element method for "discrete" crack modelling of fracture processes - Maier, Giulio; Frangi, Attilio (Computer Assisted Methods in Engineering and Science, 2023)
Analysis of fracture processes in structures of quasi-brittle concrete-like materials is here discussed on the basis of discrete cohesive crack models and of a nontraditional boundary element method. This method, called "symmetric Galerkin BEM", is characterized by the combined use of static and kinematic sources (i.e. traction and displacement discontinuities) to generate a symmetric integral operator by its spacediscrclization in the Galerkin weighted-residual sense. Consistently, the discrete crack model is enforced in a weak sense and expressed in terms or Prager's generalized variables. On this basis, some of the main aspecls of a computational theory of quasi-brittle fracture mechanies are presented and discussed.